Probing the dynamics of three freshwater Anammox genera at different salinity levels in a partial nitritation and Anammox sequencing batch reactor treating landfill leachate. (January 2021) - Huang, Xiaowu; Mi, Wenkui; Ito, Hiroaki; Kawagoshi, Yasunori
Graphical abstract: Highlights: PN/A achieved robust NRRs of 0.97 ± 0.05 kg N/m 3 /d with leachate at salinity of 3%. High affinity for nitrite and fast growth rate determined the dominance of Brocadia. Kuenenia conquered Brocadia owing to merits of Na + regulation and smf utilization. Beneficial symbiotes boosted Kuenenia's dominance at high salinity. Salt-adapted FAB could be superior than MAB to treat NH4 + -rich saline wastewater. Abstract: Partial nitritation/Anammox was applied to treat NaCl-amended landfill leachate. The reactor established robust nitrogen removal of 85.7 ± 2.4% with incremental salinity from 0.61% to 3.10% and achieved 0.91–1.05 kg N/m 3 /d at salinity of 2.96%–3.10%. Microbial community analysis revealed Nitrosomonas, Nitrospira, and denitrifiers occupied 4.1%, <0.2% and 10.9%, respectively. Salinity variations impelled the dynamics of Anammox bacteria. Jettenia shifted to Brocadia and Kuenenia at salinity of 0.61%–0.81%. Kuenenia outcompeted Brocadia and occupied 51.5% and 50.9% at salinity of 1.48%–1.54% and 2.96%–3.10%, respectively. High nitrite affinity and fast growth rate were proposed as key factors fostering Brocadia overgrew Jettenia. Functionalities of sodium-motive-force facilitated energy generation and intracellular osmotic pressure equilibrium regulation crucially determined Kuenenia's dominance at elevated salinity. Co-occurrence network further manifested beneficial symbiotic relationships boosted Kuenenia's preponderance. Knowledge gleaned deepen understanding on survival niches of freshwater Anammox genera at saline environments and lead to immediate benefits to its applications treating relevant wastewaters.